2018
DOI: 10.1002/pat.4445
|View full text |Cite
|
Sign up to set email alerts
|

Radical processes initiated by ionizing radiation in PEEK and their macroscopic consequences

Abstract: Poly (ether ether ketone) was irradiated with gamma rays or electron beam to investigate the radical process. The generated paramagnetic species were observed by electron spin resonance spectroscopy at ambient temperature and in liquid nitrogen. The effect of microwave power on saturation of the particular spectra and thermal annealing effects were determined. The following radicals were identified: radical anion, phenoxyl radical, and phenylperoxy radical. Despite the fact that the intermediates were formed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Irradiated samples show an overall decline of their thermal stability. Under nitrogen atmosphere, the temperature position of peak maximum and peak intensity of the primary degradation decrease with an increasing dose which is consistent with the study of Kornacka [12]. An increase in the peak width with dose is also observed.…”
Section: Thermal Stability Of Pristine and Irradiated Samplessupporting
confidence: 90%
See 1 more Smart Citation
“…Irradiated samples show an overall decline of their thermal stability. Under nitrogen atmosphere, the temperature position of peak maximum and peak intensity of the primary degradation decrease with an increasing dose which is consistent with the study of Kornacka [12]. An increase in the peak width with dose is also observed.…”
Section: Thermal Stability Of Pristine and Irradiated Samplessupporting
confidence: 90%
“…This increase is observed as well by dielectric measurements which also brought into evidence a wider relaxation time distribution [11]. More recently, Kornacka et al investigated the effect of electronic irradiations on PEEK in order to identify radical compounds formed during ageing [12]. They also observed a decrease in thermal stability.…”
Section: Introductionmentioning
confidence: 70%
“…Low-energy proton irradiation has a great effect on the molecular structure of PEEK materials. It has been shown that heavy ion irradiation can destroy benzene rings and generate a large number of aromatic fragments according to the references [ 26 ]. It can be inferred that the low-energy proton irradiation will destroy the carbon skeleton of the benzene ring in the molecular structure of PEEK, resulting in the decrease of C=O and benzene content in PEEK.…”
Section: Resultsmentioning
confidence: 99%
“…16 The subsequent transient chemical reactions of highly reactive species will lead to creation of excessive double bonds, 17 production of low mass stable degradation products, large cross-linked structures and eventually oxidized structures. 18,19 As an important polymer material for space applications, it is necessary to study the radiation effects of charged particles. Since its first commercialized by Imperial Chemical Industries in 1978, numerous studies have focused on the behavior of PEEK and its composites under different radiation sources such as electrons, protons, gamma rays, ultraviolet light or under combined aging.…”
Section: Introductionmentioning
confidence: 99%
“…In the specific case of electronic irradiations, Sasuga et al 20 studied the mechanical behavior evolution of irradiated samples. More recently, Kornacka et al 19 investigated the effect of electronic irradiations on PEEK in order to identify radical compounds formed during aging. So far, there have been few literatures on the ion irradiation effect of PEEK.…”
Section: Introductionmentioning
confidence: 99%